Makerere University archives, 1899- - Makerere University
Comprising of papers relating to the foundation of the University; r ecords of the principals for example Bernard De Bunsen, C. G. Turner, Y. K. Lule, Dr. Lamount etc, Chancellor and vice chancellor e.g. Milton Obote, Sentenza Kajubi and Apollo Nsibambi; records of the University Council e.g minutes, reports, correspondence, Finance Planning and Deve lopment Committee, Staff development committee, Estates committee, Visi tation committee, Student Affairs and Disciplinary Committee, Appointme nt's Board and University Secretary. It also has University Senate reco rds; Academic Board records, Academic Registrar, University Library, Re search and publications Board records, Scholarship and fellowship recor ds; Staff and personalities, General univesity records; Miscellaneous r ecords and University of East Africa records, Inter-university Council for Higher Education, Committee on needs and priorities, University Dev elopment Committee, East Africanisation Sub-committee, Committee of lib rarians records, Executive Committee, Standing Committee, University co uncil, Provincial Council, Royal College Nairobi, University college Da r es Salaam etc.
AR/MAK
English unless otherwise specified
Shelf no.2
Keywords: Makerere University -- Archives; Universities and colleges -- Uganda; Education, Higher -- Uganda